Use of Immediate Postpartum Long-Acting Reversible Contraception Before and After a State Policy Mandated Inpatient Access. Issue 5 (November 2021) - Brant, Ashley R.; Kollikonda, Swapna; Yao, Meng; Mei, Lin; Emery, Jonathan
Abstract : OBJECTIVE: To assess the rate of immediate postpartum long-acting reversible contraceptive (LARC) use in a multihospital health care system 2 years before and after the policy was implemented, and to assess factors associated with LARC use and repeat pregnancy rates within 12 months after delivery. METHODS: We conducted a retrospective chart review of all patients giving birth at three Cleveland Clinic Ohio hospitals from July 1, 2015, to June 30, 2019. We reviewed the inpatient medication reconciliation to identify the LARC initiation rate. We compared all patients who received inpatient postpartum LARC to a 1:3 matched sample of patients who did not receive LARC, matched by delivery date and location, to identify patient characteristics associated with LARC use. The electronic medical record (Epic) was reviewed to identify new pregnancies occurring within 12 months postdelivery. RESULTS: We identified 17, 848 deliveries prepolicy and 18, 555 deliveries postpolicy. Immediate postpartum LARC was used by 0.5% (monthly range 0–2.1%) of patients prepolicy and 11.6% (monthly range 8.3–15.4%) of patients postpolicy. Levonorgestrel intrauterine devices (IUDs) were used by 56.5%, implants by 29.1%, and copper IUDs by 14.5% of LARC users. Characteristics associated with LARC use included younger age, public insurance, non-White race, Hispanic or Latina ethnicity, higher body mass index, sexually transmitted infection in pregnancy, and tobacco use. Long-acting reversible contraceptive users had a lower rate of repeat pregnancy at 12 months postpartum compared with the non-LARC group (1.9% vs 3.6%, P <.001). CONCLUSION: Immediate postpartum LARC use increased after a state policy change mandated universal access and was associated with decreased pregnancy rates in the first year postdelivery. Abstract : Implementation of a state policy mandating universal access to immediate postpartum long-acting reversible contraception (LARC) was associated with a 11.1% increase in inpatient LARC initiation.